Representasi Resistensi Rasisme dalam Film Harriet 2019 - Faishal Al Ghifari (Titian: Jurnal Ilmu Humaniora, 2021)
This article discusses the representation of racism resistance in Harriet's film. This film shows how the struggle of a Harriet who tries to alleviate cases of slavery experienced by his people. From the beginning of the film, various forms of racist resistance were shown in the form of scenes and dialogues. The focus of this research is to reveal various descriptions of racism resistance through the building blocks of a film. The elements that build Harriet's film are considered to have a big role in the production process of interpreting racism resistance to the audience. This article argues that the elements contained in this film, be it narrative elements or cinematic elements, both have a huge contribution in emphasizing the image of the resistance to racism during the "Harriet Tubman" era in America. This research uses Amy Villarejo's cinematic approach and Hall's concept of representation by analyzing the data contained in the film in the form of scenes and dialogues. From the data analyzed, it is found that Harriet's character shows a dominant description of racism resistance, which is shown through scenes and dialogues in the film. Keywords: Film, Semiotics, Representation, Resistance, Racism